Aristotle’s Three Logical Figures: A Proposed Reconstruction - Netz, Reviel (Phronesis, 2023)
Based on the evidence of the likely near-contemporary mathematical practice of diagrams, this article proposes a possible reconstruction of Aristotle’s three figures as introduced in Prior Analytics 1.4–6.